Perimestike As A Value System of Islamic Philosophy In Social Interaction With Indonesian Gayo Society - Syukri Syukri; Sabariah Sabariah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The entire order of life has experienced social changes and a shift in values, including the traditional speech of the Gayo community, known as